Tower Crane Remote Wireless Monitoring System Based on Modbus/Tcp Protocol - Bo Li; Geng Chen; Le Wang; Zhe Hao (2017 IEEE International Conference on Computational Science and Engineering (CSE) and IEEE International Conference on Embedded and Ubiquitous Computing (EUC), 2017)
The wireless monitoring and management system of tower crane based on Modbus / TCP protocol is designed for the distributed, efficient and safe operation of tower crane. Designing monitor surveillance terminal with Cortex A8 and WinCE6 as platform for real-time monitoring of state information of tower crane operation. And then, Using Modbus / TCP protocol to design a wireless communication message, through GPRS and the two-way communication of remote management center, and to achieve the tower group of remote monitoring and unified management. The field operation proves that the system performance is stable and reliable, and has good application prospect.